Cost Effectiveness Of Type 2 Diabetes Patients: A Research Framework - SULAIMAN, SUZANA; SAHOL, NAZREEN (Archives of Business Research, 2020)
The growing of Metabolic Syndrome (MS) has contributed to higher risk and costs in managing Type 2 Diabetes patients. Diabetes patients are exposed to develop serious health complications. It can lead to related diseases affecting heart, eyes, kidneys, nerves and teeth. There is no proper framework on operation management and cost effectiveness in treating diabetes patients in Malaysia. Hence, it demanded on the elements and associated costs incurred by both healthcare provider and patients. This paper adopted five stages in analyzing its relevant literatures. Cost effectiveness, healthcare provider, operation management and self-management were the literatures studied. It also highlighted on management accounting gained its relevancy and contribution towards health industry. As a result, a cost effectiveness of Type 2 Diabetes framework was developed. Cost effectiveness is a key component in determining value for money. This framework provides the value for money model for Type 2 Diabetes patients. The framework clearly provides the components of cost-effectiveness and 3Es: Economy, Efficiency; Effectiveness. Objectives, resources, input, processes, output, outcomes (intended or intended) and other influences are the components.